Factor Endowments, Technology, Capital Mobility and the Sources of Comparative Advantage in Manufacturing - Hakobyan, Shushanik (World Bank, Washington, DC, 2016)
Using data on net exports and factor endowments for more than 100 countries, this paper studies the relationship between factor endowments and comparative advantage in 28 manufacturing sectors between 1975 and 2010. The authors allow for systematic technological differences across countries, including differences in factor intensities across countries with different ratios of skilled labor over unskilled labor. Capital seems to be a source of comparative disadvantage in manufacturing, and skilled labor is a source of comparative advantage in the global sample. However, skilled labor is a source of comparative disadvantage in economies with low human capital, whereas it is a source of comparative advantage in the sample of countries with high human capital. The authors attribute this heterogeneity to the rise of capital mobility across countries, particularly since the mid-1990s.